Orlando, Florida’s Urban and Community Forests and Their Ecosystem Services - Edem K. Ekpe; Elizabeth Becker; Jessica Lab; Ross Hinkle; Francisco Escobedo (EDIS, 2012)
Urban forests, or the trees and shrubs on these land uses, play an important role in providing ecosystem services and are often key components in urban planning and management as well as in environmental regulations. This 10-page fact sheet provides information, based on an assessment of urban forests within the limits of the City of Orlando conducted during the summer of 2010, on the structure and composition of Orlando's urban forest, the occurrence of invasive trees in the city, the ecosystem services trees provide, including estimating the mitigation of climate change effects and their role in urban hydrology, and how this information can be used to define sustainable urban planning objectives and goals. Written by Edem Empke, Elizabeth Becker, Jessica Lab, Ross Hinkle, and Francisco Escobedo, and published by the UF Department of School of Forest Resources and Conservation, February 2012.